(untitled) (Acta Polytechnica CTU Proceedings, 2016)
Prediction of train running and IT support of conflict resolution decision for an efficient use of the existing railway infrastructure is needed. To meet these requirements standardized interfaces between infrastructure managers and railway undertakings and infrastructure description are indispensable.